2013
DOI: 10.1002/pssa.201228776
|View full text |Cite
|
Sign up to set email alerts
|

Flexible organic field-effect transistor fabricated by thermal press process

Abstract: High throughput printing processes have been developed for the fabrication of organic flexible sheet devices. However, printing processes inevitably use toxic solvents to prepare inks of organic semiconductors. Here we propose a novel and complementary method for the preparation of flexible sheet electronics. A thermal pressing method has several advantages, such as (i) being solvent-free, (ii) resulting in flexible device with structural durability against bending, (iii) making simultaneous sealing available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…We have also carried out experiments on flexible organic field effect transistors (FETs) using the thermal press method . The thermal press method is a method by which to make organic thin film transistors by melting and spreading organic materials between two flexible films.…”
Section: Introductionmentioning
confidence: 99%
“…We have also carried out experiments on flexible organic field effect transistors (FETs) using the thermal press method . The thermal press method is a method by which to make organic thin film transistors by melting and spreading organic materials between two flexible films.…”
Section: Introductionmentioning
confidence: 99%
“…Two substrates were prepared using the same procedures described in our previous work [26][27][28][29]. The first substrate was a thin hybrid polyimide film (POMI-RAN N) provided by Arakawa Chemical Industries, Ltd., Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Although inkjet and other printers designed for printed electronics are already commercially available, solventfree printing is not. We previously developed a solventfree thin-film fabrication process that involves thermal pressing [26], thermal lamination [27,28], and ultrasonic * Corresponding Author: sakai@faculty.chiba-u.jp welding [29]. A thermal press was developed to prepare thin films of organic materials by thermally compressing the organic materials with two planar clamps [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoue et al. demonstrated that they integrated a thermal pressing method with melt‐recrystallization to fabrication OFETs on a plastic film . The semiconductor material with a low melting point could be melted and compressed with pressure to gain a thin active layer.…”
Section: Crystal Growth Strategies For Oscssmentioning
confidence: 99%